Recycled polyester pore-foaming agent as well as preparation method and application thereof
By conducting a transesterification reaction between waste polylactic acid and aliphatic dibasic acid and polycondensation reaction with other materials, regenerated polyester pore-generating agents are prepared, which solves the problem of environmental hazards of pore-generating agents, and achieves efficient and environmentally friendly preparation of porous fibers, reducing production costs.
Patent Information
- Application Number
- CN202510251819.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing pore-causing agents cause harm to the environment during the pore-causing process, and the preparation method of porous fibers has problems such as complex production steps, difficulty in scale, unenvironmental processes, and high costs.
By transesterification reaction of waste polylactic acid and aliphatic dibasic acid, a double-terminal carboxylic polylactic acid oligomer was prepared, and polycondensation reaction was carried out with polyether diol, oligomer diol and inorganic porous materials, a regenerated polyester porogenic agent containing water-soluble polylactic acid and inorganic porous materials was prepared.
It realizes efficient recycling and reuse of used polylactic acid, reduces environmental pollution, simplifies the process, reduces production costs, and prepares porous fibers with excellent performance and environmental protection characteristics.
Smart Images

Figure CN119735795A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyester recycling and reuse, and relates to a regenerated polyester porogen and a preparation method and application thereof. Background Art
[0002] Porous fibers have important uses in the fields of absorption and adsorption due to their large aspect ratio and high specific surface area. The particularity of their structure enables porous fibers to exhibit advantages such as good compression rebound, high stability, excellent thermal insulation and warmth retention, and great potential for modification and expansion of applications. Polyester porous fibers, in particular, have a broader demand in the field of textiles and clothing. Although a variety of methods such as coaxial wet spinning, electrostatic rotary spinning, micro-extrusion foam spinning, and melt-blown spinning have been used to prepare porous fibers and have proven technical stability and the ability to replicate various pore structures, these methods generally have problems such as complex production steps, difficulty in scalability, environmentally unfriendly processes, and high costs. Therefore, the industry is in urgent need of a method for preparing porous polyester fibers that is eco-friendly, low-cost, and scalable.
[0003] The patent with the authorization announcement number CN114775106B discloses a method for preparing a porous structure low-melting point composite polyester fiber, which forms micropores with a diameter of 0.1-1.0 microns on the surface of the composite fiber through alkali treatment under certain conditions; the patent application with the publication number CN118814313A provides a highly efficient moisture-absorbing and quick-drying porous polyester fiber, polyester fabric and its preparation method. However, none of the above patent technologies take into account the harm of porogens to the environment during the pore-forming process. The current water-soluble polyester is difficult to degrade in the natural environment, and exists as microplastics in every corner of the environment after being discarded, which does not conform to the current green and low-carbon concept. In addition, pore-forming treatment methods such as high-temperature and high-pressure dyeing or alkali treatment will also produce a large amount of waste liquid, which must be neutralized before discharge.
[0004] Based on the environmental problems caused by the current application of porogens, a green method for preparing porous fibers is urgently needed. Polylactic acid, as a degradable polyester derived from renewable plant resources, is widely used in packaging, textiles, medicine and other fields, and is vigorously promoted as an environmentally friendly material. However, the mass production and use of polylactic acid will also produce a large amount of waste polylactic acid. If this part of polylactic acid directly enters the environment, although it is biodegradable, degradation requires specific conditions, and degradation to carbon dioxide and water is difficult to achieve rapid and direct utilization, which is actually a waste of resources.
[0005] Energy recovery and mechanical recycling are common ways to solve the waste of PLA resources, but the former will lead to high pollution with low return rate, and the latter is usually accompanied by the degradation of plastic performance. Chemical recycling can not only provide a sustainable source of plastic raw materials, but also effectively reduce the environmental pollution caused by waste plastics. However, existing chemical recycling methods, such as the methods reported in the patent application with publication number CN118459435A and the patent with authorization announcement number CN102746270B, require cumbersome post-processing procedures such as separation and purification in order to obtain recycled polylactic acid (PLA).
[0006] The literature (A “Polymer to Polymer” Chemical Recycling of PLA Plastics by the “DE–RE Polymerization” Strategy, Macromolecules 2022, 55, 5, 1726–1735) dissolves PLA in dichloromethane, degrades PLA using different catalysts and an appropriate amount of methanol, and then adds lactic acid to the degradation product to further polymerize it into PLA. The literature (Vitrimeric Polylactide by Two-step Alcoholysis and Transesterification during Reactive Processing for Enhanced Melt Strength ACSAppl. Mater. Interfaces 2022, 14, 40, 45966–45977) esterifies polylactic acid with glycerol and adds a chain extender to recycle PLA into Vitrimer (a plastic thermosetting resin) to improve the melt strength during the foaming process. However, these methods have problems such as the addition of additional monomers, the use of toxic reagents, cumbersome steps and decreased product properties (such as mechanical properties), which are not conducive to industrial applications. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and provide a regenerated polyester porogen and a preparation method and application thereof.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a recycled polyester porogen from waste polylactic acid, comprising: firstly subjecting the waste polylactic acid to an ester exchange reaction with an aliphatic dibasic acid to obtain a double-terminal carboxyl polylactic acid oligomer, and then mixing the double-terminal carboxyl polylactic acid oligomer, a polyether diol, an oligomer diol and an inorganic porous material to a polycondensation reaction to obtain a recycled polyester porogen containing water-soluble polylactic acid and an inorganic porous material;
[0010] The carbon number of the aliphatic dibasic acid is 4-20; if the carbon number of the aliphatic dibasic acid is greater than 20, and the carbon chain of the aliphatic dibasic acid is too long, on the one hand, the reaction activity of the terminal carboxyl group of the aliphatic dibasic acid is low, and if the time of the transesterification reaction is not extended, the transesterification reaction will not be thorough enough, and the effective preparation of the double-terminal carboxyl polylactic acid oligomer cannot be achieved. If the time of the transesterification reaction is extended, the thermal degradation of the waste polylactic acid will become serious; on the other hand, since the aliphatic dibasic acid needs to enter the molecular chain of the polylactic acid during the transesterification reaction, the excessively long carbon chain of the aliphatic dibasic acid will cause the regularity of the molecular chain of the polylactic acid to be excessively destroyed, thereby affecting the crystallization performance of the final water-soluble polylactic acid, and further affecting the spinning process; if the carbon chain of the aliphatic dibasic acid is too short, its thermal stability is very poor, it will volatilize at the transesterification temperature, and the waste polylactic acid cannot be depolymerized;
[0011] The number average molecular weight of the double-end carboxyl polylactic acid oligomer is 1000-8000 g / mol; if the molecular weight of the double-end carboxyl polylactic acid oligomer is too low, the crystallization ability of the water-soluble polylactic acid will be low, thereby affecting the spinning process; if the molecular weight of the double-end carboxyl polylactic acid oligomer is too high, an uneven reaction will occur during the repolymerization process, ultimately causing the molecular weight distribution of the water-soluble polylactic acid to be too wide, thereby affecting the spinning process;
[0012] The degree of polymerization of the double-terminated carboxyl polylactic acid oligomer is 12-110;
[0013] The oligomer diol is obtained by esterification of 5-sodium sulfoisophthalic acid and aliphatic diol;
[0014] The degree of polymerization of the oligomer diol is 2-5.
[0015] As the preferred technical solution:
[0016] The method for preparing a recycled polyester porogen from waste polylactic acid as described above, the preparation process of the double-terminal carboxyl polylactic acid oligomer is: adding waste polylactic acid, aliphatic dibasic acid, and a first catalyst into a reaction kettle, reacting at 150-220° C. and 0.01-0.3 MPa for 2.5-5 hours, and obtaining the double-terminal carboxyl polylactic acid oligomer;
[0017] Among them, the mass of aliphatic dibasic acid , the quality of waste polylactic acid , Relative molecular weight of aliphatic dibasic acids , Theoretical value of number average molecular weight of double-terminated carboxyl polylactic acid oligomer The relationship satisfies the following formula:
[0018] ;
[0019] In the formula, , The unit is g; , The unit of is g / mol; φ is 17g / mol;
[0020] The mass of the first catalyst is 100-1000ppm of the mass of the waste polylactic acid; the first catalyst is one or more of ethylene glycol titanium, tetrabutyl titanate, ethylene glycol antimony, antimony acetate, antimony oxide, stannous octoate, stannous chloride, zinc acetate and zinc oxide;
[0021] The derivation process of the above formula is as follows: According to the preparation process of the double-terminal carboxyl polylactic acid oligomer, the structural formula of the double-terminal carboxyl polylactic acid oligomer can be inferred to be (wherein R is the chain segment between two carboxyl groups in the aliphatic dibasic acid, and n is the number of repeating units of lactic acid);
[0022] It can be seen that it includes n lactic acid repeating units and 1 aliphatic dibasic acid; the relative molecular mass of the lactic acid chain segment is 72, and the aliphatic dibasic acid will remove 1 -OH (molar mass is 17g / mol, recorded as φ) when the end capping is performed. Assuming that the theoretical number average molecular weight of the double-terminated carboxyl polylactic acid oligomer is , then we can list formula 1:
[0023] =72n+ -φ; Formula 1
[0024] Transformation to get formula 2:
[0025] n=( - +φ) / 72; Formula 2
[0026] Assume that the mass of waste polylactic acid added during the preparation process is The molar number of lactic acid segments in waste polylactic acid is n PLA , then we can list formula 3:
[0027] n PLA =m / 72; Formula 3
[0028] It can be obtained that the number of lactic acid chains in waste polylactic acid is n more than that in the designed double-terminal carboxyl polylactic acid oligomer. PLA / n times, the multiple is the molar number n of the required aliphatic dibasic acid COOH , we get formula 4:
[0029] n COOH =n PLA / n; Formula 4
[0030] Substituting equation 3 into equation 4, we get equation 5:
[0031] n COOH =m / (72n); Formula 5
[0032] The relative molecular mass of aliphatic dibasic acids It can be calculated according to formula 6:
[0033] =n COOH × ; Formula 6
[0034] Substituting equation 5 into equation 6, we get equation 7:
[0035] =(m× ) / (72n); Formula 7
[0036] Finally, substitute equation 2 into equation 7 to obtain the above formula;
[0037] Experiments show that the relative deviation of the number average molecular weight of double-end carboxyl polylactic acid oligomers does not exceed 2%, and the relative deviation = (|actual value-theoretical value| / theoretical value) × 100%. The above formula can be used to guide production. After determining the target number average molecular weight of double-end carboxyl polylactic acid oligomers, the appropriate aliphatic dibasic acid can be selected according to the above formula, and the quality of the aliphatic dibasic acid and the quality of waste polylactic acid can be determined.
[0038] The method for preparing a recycled polyester porogen from waste polylactic acid as described above, the preparation process of the oligomer diol is as follows: adding sodium 5-sulfonate of isophthalic acid, aliphatic diol and a second catalyst into a reaction kettle, reacting at 220-240°C and 0.1-0.3MPa until the water output reaches more than 95% of the theoretical water output, thereby obtaining the oligomer diol;
[0039] The molar ratio of 5-sodium sulfoisophthalic acid to aliphatic diol is 1:1.01-1.1, and the mass of the second catalyst is 0-500ppm of the mass of 5-sodium sulfoisophthalic acid;
[0040] The reaction was accompanied by stirring at a speed of 100-200 r / min;
[0041] The aliphatic diol is one or more of ethylene glycol, propylene glycol, butanediol and pentanediol; the second catalyst is one or more of ethylene glycol titanium, tetrabutyl titanate, ethylene glycol antimony, antimony acetate, antimony oxide, stannous octoate, stannous chloride, zinc acetate and zinc oxide.
[0042] In the method for preparing a recycled polyester porogen from waste polylactic acid as described above, the polyether diol is one or more of polyethylene glycol, polypropylene glycol and polytetrahydrofuran, and the number average molecular weight of the polyether diol is 400-4000 g / mol.
[0043] In the method for preparing a recycled polyester porogen from waste polylactic acid as described above, the inorganic porous material is one or more of a porous carbon material and a porous natural mineral powder, the average particle size is not less than 0.05 microns, and the average pore size of the micropores does not exceed 200 nanometers.
[0044] As described above, in a method for preparing a recycled polyester porogen from waste polylactic acid, the total molar amount of polyether diol and oligomer diol is 1.0-1.1 times the molar amount of waste polylactic acid, the molar amount of oligomer diol is 10-30% of the total molar amount of polyether diol and oligomer diol, and the mass of the inorganic porous material is not less than 5% of the mass of the waste polylactic acid.
[0045] As described above, a method for preparing a recycled polyester porogen from waste polylactic acid, the polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction, the pre-polycondensation reaction has a pressure of 0.01-0.1MPa, a temperature of 170-230°C, and a time of 1-3h, and the final polycondensation reaction has a pressure of 5-300Pa, a temperature of 180-250°C, and a time of 3-5h.
[0046] The present invention also provides a recycled polyester porogen, which is prepared by a method for preparing a recycled polyester porogen from waste polylactic acid as described in any one of the above items; the recycled polyester porogen has a number average molecular weight of 14000-33000 g / mol, a molecular weight distribution index of 1.5-3.0, a melting point of 80-180°C, a crystallization temperature of 25-60°C, and a mass loss rate of 10-75% when immersed in hot water at 50-100°C for 3-30 minutes.
[0047] The present invention also provides an application of the above-mentioned regenerated polyester porogen, wherein the regenerated polyester porogen and fiber-grade polyester are melt-blended and spun to obtain blended fibers, and then the blended fibers are immersed in hot water at 50-100° C. for 3-30 minutes to obtain porous fibers.
[0048] As the preferred technical solution:
[0049] As described above, the number average molecular weight of the fiber-grade polyester is 15000-40000 g / mol, the mass of the recycled polyester porogen is 2-30% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fiber to hot water is 1:10-50; the fineness of the porous fiber is 1.0-5.0 dtex, the breaking strength is 2.5-5.5 cN / dtex, and the elongation at break is 10-40%; the porous fiber has a porous structure with an average pore size of 50-300 nm; the specific surface area of the porous fiber is increased by 1.5-12.5 times relative to the blended fiber, and the mass is reduced by 2-30wt%.
[0050] The principle of the present invention is as follows:
[0051] The invention designs a dicarboxyl polylactic acid oligomer through ester exchange reaction, and prepares a regenerated polyester porogen containing water-soluble polylactic acid and inorganic porous material with polyether diol and oligomer diol, thereby realizing the recycling of waste polylactic acid.
[0052] The water-soluble polylactic acid in the regenerated polyester porogen prepared by the present invention has good water solubility due to the presence of hydrophilic polyether segments and sodium sulfonate groups in the molecular chain. During the dissolution process, the hydrophilic polyether segments exist in the water-soluble polylactic acid in an amorphous form, which can promote water molecules to enter the amorphous region; the presence of the sodium sulfonate group can quickly capture the water molecules entering the water-soluble polylactic acid molecular chain, thereby dissolving the water-soluble polylactic acid molecular chain in water, and the entire dissolution process presents a phenomenon of swelling first and then dissolving.
[0053] Introducing 5-sodium sulfoisophthalate into water-soluble polylactic acid will cause its crystallization ability to decrease, making it difficult to carry out melt spinning processing. To this end, on the one hand, the present invention controls the carbon number of the aliphatic dibasic acid and the number average molecular weight of the double-terminated carboxyl polylactic acid oligomer, so that the crystallization performance of the water-soluble polylactic acid can be guaranteed. On the other hand, the present invention introduces the inorganic porous material into the polymerization system of the water-soluble polylactic acid by in-situ polymerization, which not only avoids the agglomeration of the inorganic porous material in the polymerization system, but also can use the inorganic porous material as a nucleating agent to promote the crystallization of the water-soluble polylactic acid.
[0054] When the recycled polyester porogen containing water-soluble polylactic acid and inorganic porous material is melt-blended with fiber-grade polyester for spinning, the presence of polylactic acid segments in the water-soluble polylactic acid enables the water-soluble polylactic acid to have good compatibility with the fiber-grade polyester, thereby ensuring the uniform distribution of the water-soluble polylactic acid in the fiber-grade polyester. The incompatibility between the polyether segments in the water-soluble polylactic acid and the fiber-grade polyester forms a phase separation structure between the water-soluble polylactic acid and the fiber-grade polyester, thereby avoiding the water-soluble polylactic acid from being completely coated by the fiber-grade polyester.
[0055] Beneficial effects:
[0056] (1) The present invention realizes the efficient recycling and reuse of waste polylactic acid, improves the resource utilization rate of polylactic acid, and reduces resource waste.
[0057] (2) The porous fiber prepared by the method of the present invention does not produce waste liquid that is harmful to the environment during the pore-forming process and does not require secondary treatment, which is in line with the green and low-carbon environmental protection concept.
[0058] (3) The preparation method of the present invention has simple process, convenient operation, and is easy to realize large-scale production, thereby reducing the production cost of the porous fibers.
[0059] (4) The porous fibers prepared by the present invention have independent microporous structures and high specific surface area, which can firmly lock the circulating air and can be used as thermal insulation fiber materials. At the same time, the mechanical properties of the fibers are also effectively guaranteed, meeting the performance requirements of porous fibers in the fields of textiles and clothing.
[0060] (5) The porous fibers prepared by the present invention have excellent performance and environmental protection characteristics, and can be widely used in the fields of textiles and clothing, absorbent materials, adsorption materials, etc., and have broad market prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is the nuclear magnetic resonance spectrum of the double-terminal carboxyl polylactic acid oligomer prepared in Example 6, wherein a is the methylene H close to the carbonyl group in adipic acid, b is the methine H far from the carbonyl group in adipic acid, c is the methine H in the polylactic acid repeating unit, and d is the methyl H in the polylactic acid repeating unit. DETAILED DESCRIPTION
[0062] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0063] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0064] Intrinsic viscosity: Use an Ubbelohde viscometer with a capillary diameter of 0.7-0.8mm for testing. Use an electronic balance to take 0.25g of the sample to be tested, dissolve it in a mixed solvent of phenol and tetrachloroethane with a mass ratio of 1:1 in a 60-70℃ water bath to obtain a test solution with a concentration of 0.005g / ml. Then put the test solution in a 25±0.1℃ constant temperature water bath for 10 minutes, observe and record the test solution flowing through the upper and lower scale lines of the Ubbelohde viscometer (at the same time set up a control group, the only difference from this test is that the test sample is not added), the test is carried out in parallel 3 times and the average value is taken as the final result. The calculation process is according to the following formula:
[0065] ;
[0066] ;
[0067] ;
[0068] Where η r is the relative viscosity, is the flow time of the solution to be tested (s), is the flow time of the mixed solvent of phenol and tetrachloroethane in the control group (s), η sp To increase specific viscosity, is the intrinsic viscosity (dL / g), and c is the concentration of the solution to be tested (g / ml).
[0069] Degree of polymerization: 5-10 mg of the sample to be tested was dissolved in 0.55-0.6 mL of deuterated chloroform (CDCl3) to obtain a test solution, which was tested by Avance-600 Hz nuclear magnetic resonance spectrometer (NMR); wherein the number of scans was 64 times.
[0070] Number average molecular weight and molecular weight distribution index: tested by Agilent 1260 gel permeation chromatography (GPC), the chromatographic column is Agilent HFIP series, the mobile phase consists of hexafluoroisopropanol and sodium trifluoroacetate (the concentration of sodium trifluoroacetate is 0.02 mol / L), and the test temperature is 35°C.
[0071] Melting point, crystallization temperature: Tested in accordance with GB / T 19466.3-2004 Plastics Differential Scanning Calorimetry (DSC) Part 3: Determination of Melting and Crystallization Temperature and Thermal Enthalpy.
[0072] Mass loss rate after soaking in hot water at 50-100℃ for 3-30min: Weigh 10-15g of the sample to be tested and record its weight as (unit: g), soak it in water at a temperature of 50-100℃ for 3-30min, then take it out, dry it at 50℃, and weigh it again (recorded as , unit g), use the following formula to calculate the mass loss rate :
[0073] .
[0074] Denier: Tested according to GB / T 14343-2008.
[0075] Breaking strength: tested according to GB / T 14344-2022.
[0076] Elongation at break: tested according to GB / T 14344-2022.
[0077] Specific surface area: The specific surface area of the fiber was measured using an Autosorb-iQ fully automatic rapid specific surface and porosity analyzer.
[0078] Example 1
[0079] A method for preparing porous fibers, the specific steps are as follows:
[0080] (1) Preparation of raw materials;
[0081] Waste polylactic acid: intrinsic viscosity is 1.20dL / g;
[0082] Aliphatic dibasic acid: adipic acid;
[0083] First catalyst: tetrabutyl titanate;
[0084] Sodium 5-sulfoisophthalate;
[0085] Aliphatic diols: ethylene glycol;
[0086] Polyether diol: polyethylene glycol, number average molecular weight 400 g / mol;
[0087] Inorganic porous material: diatomaceous earth, with an average particle size of 2 microns and an average pore size of 100 nanometers;
[0088] Fiber-grade polyester: polylactic acid, number average molecular weight 40000 g / mol;
[0089] (2) preparing double-terminated carboxyl-containing polylactic acid oligomers and oligomer diols respectively;
[0090] The preparation process of the double-terminal carboxyl polylactic acid oligomer is as follows: waste polylactic acid, aliphatic dibasic acid and a first catalyst are added into a reaction kettle, and reacted at 150° C. and 0.01 MPa for 5 hours to obtain a double-terminal carboxyl polylactic acid oligomer with a number average molecular weight of 1000 g / mol and a degree of polymerization of 12;
[0091] The mass ratio of the waste polylactic acid to the aliphatic dibasic acid is 6:1, and the mass of the first catalyst is 1000ppm of the mass of the waste polylactic acid;
[0092] The preparation process of the oligomer diol is as follows: add 5-sodium sulfoisophthalic acid and aliphatic diol into a reaction kettle, and react at a temperature of 220° C. and a pressure of 0.1 MPa under stirring conditions of a stirring speed of 200 r / min until the water output reaches 99% of the theoretical water output, thereby obtaining an oligomer diol with a polymerization degree of 2; wherein the molar ratio of 5-sodium sulfoisophthalic acid to aliphatic diol is 1:1.01;
[0093] (3) Preparation of recycled polyester porogen;
[0094] After mixing double-terminal carboxyl polylactic acid oligomer, polyether diol, oligomer diol and inorganic porous material, firstly carry out pre-polycondensation reaction at 0.1MPa and 170°C for 2.5h, and then carry out final polycondensation reaction at 200Pa and 180°C for 5h, so as to obtain a regenerated polyester porogen containing water-soluble polylactic acid and inorganic porous material; wherein the total molar amount of polyether diol and oligomer diol is 1.0 times the molar amount of waste polylactic acid, the molar amount of oligomer diol is 10% of the total molar amount of polyether diol and oligomer diol, and the mass of inorganic porous material is 10% of the mass of waste polylactic acid;
[0095] The number average molecular weight of the obtained recycled polyester porogen is 14000 g / mol, the molecular weight distribution index is 1.5, the melting point is 80°C, and the crystallization temperature is 25°C; the mass loss rate of the recycled polyester porogen after soaking in hot water at 50°C for 30 minutes is 50%;
[0096] (4) Preparation of porous fibers;
[0097] After melt-blending and spinning the recycled polyester porogen with fiber-grade polyester (spinning temperature is 180°C) to obtain blended fibers, the blended fibers are immersed in hot water at 50°C for 30 minutes to obtain porous fibers; wherein the mass of the recycled polyester porogen is 2% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fibers to the hot water is 1:50.
[0098] The final porous fiber has a fineness of 1 dtex, a breaking strength of 2.5 cN / dtex, and a breaking elongation of 40%; the porous fiber has a porous structure with an average pore size of 120 nm; the specific surface area of the porous fiber is increased by 10 times compared with the blended fiber, and the weight is reduced by 25wt%.
[0099] Comparative Example 1
[0100] A method for preparing a fiber, which differs from Example 1 only in that: in step (2), when preparing a double-end carboxyl polylactic acid oligomer, the amount of waste polylactic acid added is adjusted, and the mass ratio of waste polylactic acid to aliphatic dibasic acid is 3:1, which makes the number average molecular weight of the double-end carboxyl polylactic acid oligomer be 500 g / mol and the degree of polymerization be 5.
[0101] The breaking strength of the finally prepared fiber was 2.0 cN / dtex.
[0102] Compared with Example 1, the breaking strength of the fiber is significantly reduced in Comparative Example 1. This is because the number average molecular weight of the double-end carboxyl polylactic acid oligomer in Comparative Example 1 is too low, resulting in a low crystallization ability of the water-soluble polylactic acid, and poor regularity and orderliness of the internal structure of the fiber. When stretched by external force, the molecular chains are more likely to slip and break, thereby reducing the breaking strength of the fiber.
[0103] Example 2
[0104] A method for preparing porous fibers, the specific steps are as follows:
[0105] (1) Preparation of raw materials;
[0106] Waste polylactic acid: intrinsic viscosity is 1.25dL / g;
[0107] Aliphatic dibasic acid: eicosapentadicarboxylic acid;
[0108] The first catalyst and the second catalyst: both are ethylene glycol antimony;
[0109] Sodium 5-sulfoisophthalate;
[0110] Aliphatic diols: propylene glycol;
[0111] Polyether diol: polypropylene glycol, number average molecular weight is 1000 g / mol;
[0112] Inorganic porous material: bamboo charcoal powder, with an average particle size of 0.05 microns and an average pore size of 50 nanometers;
[0113] Fiber-grade polyester: polybutylene succinate, number average molecular weight 15000 g / mol;
[0114] (2) preparing double-terminated carboxyl-containing polylactic acid oligomers and oligomer diols respectively;
[0115] The preparation process of the double-terminal carboxyl polylactic acid oligomer is as follows: waste polylactic acid, aliphatic dibasic acid and a first catalyst are added into a reaction kettle, and reacted at 160° C. and 0.08 MPa for 4 hours to obtain a double-terminal carboxyl polylactic acid oligomer with a number average molecular weight of 2000 g / mol and a degree of polymerization of 23;
[0116] The mass ratio of the waste polylactic acid to the aliphatic dibasic acid is 5:1, and the mass of the first catalyst is 800 ppm of the mass of the waste polylactic acid;
[0117] The preparation process of the oligomer diol is as follows: add 5-sodium sulfonate of isophthalic acid, aliphatic diol and a second catalyst into a reaction kettle, react at a temperature of 225° C. and a pressure of 0.15 MPa under a stirring condition of a stirring speed of 100 r / min until the water output reaches 96% of the theoretical water output, thereby obtaining an oligomer diol with a polymerization degree of 2; wherein the molar ratio of 5-sodium sulfonate of isophthalic acid to the aliphatic diol is 1:1.01, and the mass of the second catalyst is 100 ppm of the mass of 5-sodium sulfonate of isophthalic acid;
[0118] (3) Preparation of recycled polyester porogen;
[0119] After mixing double-terminal carboxyl polylactic acid oligomer, polyether diol, oligomer diol and inorganic porous material, firstly carry out pre-polycondensation reaction at 0.08MPa and 190°C for 3h, and then carry out final polycondensation reaction at 300Pa and 200°C for 4.5h, so as to obtain a regenerated polyester porogen containing water-soluble polylactic acid and inorganic porous material; wherein the total molar amount of polyether diol and oligomer diol is 1.0 times the molar amount of waste polylactic acid, the molar amount of oligomer diol is 30% of the total molar amount of polyether diol and oligomer diol, and the mass of inorganic porous material is 5% of the mass of waste polylactic acid;
[0120] The number average molecular weight of the obtained recycled polyester porogen is 18000 g / mol, the molecular weight distribution index is 3, the melting point is 100°C, and the crystallization temperature is 30°C; the mass loss rate of the recycled polyester porogen after soaking in hot water at 65°C for 25 minutes is 60%;
[0121] (4) Preparation of porous fibers;
[0122] After melt-blending and spinning the recycled polyester porogen with fiber-grade polyester (spinning temperature is 190°C) to obtain blended fibers, the blended fibers are immersed in hot water at 65°C for 25 minutes to obtain porous fibers; wherein the mass of the recycled polyester porogen is 5% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fibers to the hot water is 1:40.
[0123] The final porous fiber has a fineness of 2dtex, a breaking strength of 3cN / dtex, and a breaking elongation of 30%; the porous fiber has a porous structure with an average pore size of 50nm; the specific surface area of the porous fiber is increased by 12.5 times compared with the blended fiber, and the weight is reduced by 20wt%.
[0124] Comparative Example 2
[0125] A method for preparing fiber, which is different from Example 2 only in that the aliphatic dibasic acid used in this comparative example is tetracosanedicarboxylic acid (CAS No. 3365-67-1).
[0126] The breaking strength of the finally prepared fiber was 2.0 cN / dtex.
[0127] Compared with Example 2, the breaking strength of the fiber is significantly reduced in Comparative Example 2. This is because the carbon chain of the aliphatic dibasic acid in Comparative Example 2 is too long, resulting in insufficient ester exchange reaction and serious destruction of the regularity of the polylactic acid molecular chain, which affects the structure and properties of the final fiber and weakens its ability to resist external stretching, thereby manifesting as a reduction in breaking strength.
[0128] Example 3
[0129] A method for preparing porous fibers, the specific steps are as follows:
[0130] (1) Preparation of raw materials;
[0131] Waste polylactic acid: intrinsic viscosity is 1.30dL / g;
[0132] Aliphatic dibasic acid: suberic acid;
[0133] The first catalyst and the second catalyst: both are stannous octoate;
[0134] Sodium 5-sulfoisophthalate;
[0135] Aliphatic diols: butanediol;
[0136] Polyether diol: polytetrahydrofuran, number average molecular weight 2000 g / mol;
[0137] Inorganic porous material: graphene powder, with an average particle size of 3 microns and an average pore size of 200 nanometers;
[0138] Fiber-grade polyester: polyethylene terephthalate, number average molecular weight 25000 g / mol;
[0139] (2) preparing double-terminated carboxyl-containing polylactic acid oligomers and oligomer diols respectively;
[0140] The preparation process of the double-terminal carboxyl polylactic acid oligomer is as follows: waste polylactic acid, aliphatic dibasic acid and a first catalyst are added into a reaction kettle, and reacted at 180° C. and 0.1 MPa for 3.5 hours to obtain a double-terminal carboxyl polylactic acid oligomer with a number average molecular weight of 4000 g / mol and a degree of polymerization of 53;
[0141] The mass ratio of the waste polylactic acid to the aliphatic dibasic acid is 22:1, and the mass of the first catalyst is 500 ppm of the mass of the waste polylactic acid;
[0142] The preparation process of the oligomer diol is as follows: add 5-sodium sulfonate of isophthalic acid, aliphatic diol and a second catalyst into a reaction kettle, react at a temperature of 230° C. and a pressure of 0.2 MPa under a stirring condition of a stirring speed of 150 r / min until the water output reaches 98% of the theoretical water output, thereby obtaining an oligomer diol with a polymerization degree of 3; wherein the molar ratio of 5-sodium sulfonate of isophthalic acid to the aliphatic diol is 1:1.05, and the mass of the second catalyst is 300 ppm of the mass of 5-sodium sulfonate of isophthalic acid;
[0143] (3) Preparation of recycled polyester porogen;
[0144] After mixing double-terminal carboxyl polylactic acid oligomer, polyether diol, oligomer diol and inorganic porous material, firstly carry out pre-polycondensation reaction at 0.06MPa and 200°C for 2h, and then carry out final polycondensation reaction at 100Pa and 220°C for 4h, so as to obtain a regenerated polyester porogen containing water-soluble polylactic acid and inorganic porous material; wherein the total molar amount of polyether diol and oligomer diol is 1.1 times the molar amount of waste polylactic acid, the molar amount of oligomer diol is 20% of the total molar amount of polyether diol and oligomer diol, and the mass of inorganic porous material is 15% of the mass of waste polylactic acid;
[0145] The number average molecular weight of the obtained recycled polyester porogen is 20000 g / mol, the molecular weight distribution index is 1.6, the melting point is 120°C, and the crystallization temperature is 50°C; the mass loss rate of the recycled polyester porogen after soaking in hot water at 80°C for 15 minutes is 75%;
[0146] (4) Preparation of porous fibers;
[0147] After melt-blending and spinning the recycled polyester porogen with fiber-grade polyester (spinning temperature is 210°C) to obtain blended fibers, the blended fibers are immersed in hot water at 80°C for 15 minutes to obtain porous fibers; wherein the mass of the recycled polyester porogen is 15% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fibers to the hot water is 1:30.
[0148] The final porous fiber has a fineness of 3dtex, a breaking strength of 3.5cN / dtex, and a breaking elongation of 25%; the porous fiber has a porous structure with an average pore size of 300nm; the specific surface area of the porous fiber is increased by 1.5 times compared with the blended fiber, and the weight is reduced by 2wt%.
[0149] Example 4
[0150] A method for preparing porous fibers, the specific steps are as follows:
[0151] (1) Preparation of raw materials;
[0152] Waste polylactic acid: intrinsic viscosity is 1.35dL / g;
[0153] Aliphatic dibasic acid: sebacic acid;
[0154] The first catalyst and the second catalyst: both are zinc acetate;
[0155] Sodium 5-sulfoisophthalate;
[0156] Aliphatic diols: pentanediol;
[0157] Polyether diol: polyethylene glycol, number average molecular weight 2000 g / mol;
[0158] Inorganic porous material: sepiolite powder, with an average particle size of 1 micron and an average micropore size of 80 nanometers;
[0159] Fiber-grade polyester: poly(trimethylene terephthalate), number average molecular weight 20,000 g / mol;
[0160] (2) preparing double-terminated carboxyl-containing polylactic acid oligomers and oligomer diols respectively;
[0161] The preparation process of the double-terminal carboxyl polylactic acid oligomer is as follows: waste polylactic acid, aliphatic dibasic acid and a first catalyst are added into a reaction kettle, and reacted at 200° C. and 0.2 MPa for 3 hours to obtain a double-terminal carboxyl polylactic acid oligomer with a number average molecular weight of 6000 g / mol and a degree of polymerization of 81;
[0162] The mass ratio of the waste polylactic acid to the aliphatic dibasic acid is 29:1, and the mass of the first catalyst is 300 ppm of the mass of the waste polylactic acid;
[0163] The preparation process of the oligomer diol is as follows: add 5-sodium sulfonate of isophthalic acid, aliphatic diol and a second catalyst into a reaction kettle, react at a temperature of 235° C. and a pressure of 0.25 MPa under stirring conditions of a stirring speed of 200 r / min until the water output reaches 95% of the theoretical water output, thereby obtaining an oligomer diol with a polymerization degree of 4; wherein the molar ratio of 5-sodium sulfonate of isophthalic acid to the aliphatic diol is 1:1.05, and the mass of the second catalyst is 400 ppm of the mass of 5-sodium sulfonate of isophthalic acid;
[0164] (3) Preparation of recycled polyester porogen;
[0165] After mixing double-terminal carboxyl polylactic acid oligomer, polyether diol, oligomer diol and inorganic porous material, firstly carry out pre-polycondensation reaction at 0.04MPa and 210°C for 1.5h, and then carry out final polycondensation reaction at 50Pa and 230°C for 3.5h, so as to obtain a regenerated polyester porogen containing water-soluble polylactic acid and inorganic porous material; wherein the total molar amount of polyether diol and oligomer diol is 1.1 times the molar amount of waste polylactic acid, the molar amount of oligomer diol is 20% of the total molar amount of polyether diol and oligomer diol, and the mass of inorganic porous material is 20% of the mass of waste polylactic acid;
[0166] The number average molecular weight of the obtained recycled polyester porogen is 22000 g / mol, the molecular weight distribution index is 1.8, the melting point is 160°C, and the crystallization temperature is 40°C; the mass loss rate of the recycled polyester porogen after soaking in hot water at 70°C for 20 minutes is 65%;
[0167] (4) Preparation of porous fibers;
[0168] After melt-blending and spinning the recycled polyester porogen with fiber-grade polyester (spinning temperature is 220°C) to obtain blended fibers, the blended fibers are immersed in hot water at 70°C for 20 minutes to obtain porous fibers; wherein the mass of the recycled polyester porogen is 10% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fibers to the hot water is 1:20.
[0169] The final porous fiber has a fineness of 4 dtex, a breaking strength of 4.5 cN / dtex, and a breaking elongation of 20%; the porous fiber has a porous structure with an average pore size of 100 nm; the specific surface area of the porous fiber is increased by 8 times compared with the blended fiber, and the weight is reduced by 30wt%.
[0170] Example 5
[0171] A method for preparing porous fibers, the specific steps are as follows:
[0172] (1) Preparation of raw materials;
[0173] Waste polylactic acid: intrinsic viscosity is 1.40dL / g;
[0174] Aliphatic dibasic acid: succinic acid;
[0175] The first catalyst and the second catalyst are both a mixture of tetrabutyl titanate and zinc acetate in a mass ratio of 1:1;
[0176] Sodium 5-sulfoisophthalate;
[0177] Aliphatic diol: a mixture of ethylene glycol and butanediol in a mass ratio of 1:1;
[0178] Polyether diol: polyethylene glycol, number average molecular weight 4000 g / mol;
[0179] Inorganic porous material: diatomaceous earth, with an average particle size of 3 microns and an average pore size of 150 nanometers;
[0180] Fiber-grade polyester: polybutylene terephthalate, number average molecular weight 30,000 g / mol;
[0181] (2) preparing double-terminated carboxyl-containing polylactic acid oligomers and oligomer diols respectively;
[0182] The preparation process of the double-terminal carboxyl polylactic acid oligomer is as follows: waste polylactic acid, aliphatic dibasic acid and a first catalyst are added into a reaction kettle, and reacted at 220° C. and 0.3 MPa for 2.5 hours to obtain a double-terminal carboxyl polylactic acid oligomer with a number average molecular weight of 8000 g / mol and a degree of polymerization of 110;
[0183] The mass ratio of the waste polylactic acid to the aliphatic dibasic acid is 68:1, and the mass of the first catalyst is 100 ppm of the mass of the waste polylactic acid;
[0184] The preparation process of the oligomer diol is as follows: add 5-sodium sulfonate of isophthalic acid, aliphatic diol and a second catalyst into a reaction kettle, react at a temperature of 240° C. and a pressure of 0.3 MPa under a stirring condition of a stirring speed of 100 r / min until the water output reaches 97% of the theoretical water output, thereby obtaining an oligomer diol with a polymerization degree of 5; wherein the molar ratio of 5-sodium sulfonate of isophthalic acid to the aliphatic diol is 1:1.1, and the mass of the second catalyst is 500 ppm of the mass of 5-sodium sulfonate of isophthalic acid;
[0185] (3) Preparation of recycled polyester porogen;
[0186] After mixing double-terminal carboxyl polylactic acid oligomer, polyether diol, oligomer diol and inorganic porous material, firstly carry out pre-polycondensation reaction at 0.01MPa and 230°C for 1h, and then carry out final polycondensation reaction at 5Pa and 250°C for 3h, so as to obtain a regenerated polyester porogen containing water-soluble polylactic acid and inorganic porous material; wherein the total molar amount of polyether diol and oligomer diol is 1.0 times the molar amount of waste polylactic acid, the molar amount of oligomer diol is 30% of the total molar amount of polyether diol and oligomer diol, and the mass of inorganic porous material is 30% of the mass of waste polylactic acid;
[0187] The number average molecular weight of the obtained recycled polyester porogen is 33000 g / mol, the molecular weight distribution index is 2, the melting point is 180°C, and the crystallization temperature is 60°C; the mass loss rate of the recycled polyester porogen after soaking in hot water at 100°C for 3 minutes is 10%;
[0188] (4) Preparation of porous fibers;
[0189] After melt-blending and spinning the recycled polyester porogen with fiber-grade polyester (spinning temperature is 230°C) to obtain blended fibers, the blended fibers are immersed in hot water at 100°C for 3 minutes to obtain porous fibers; wherein the mass of the recycled polyester porogen is 30% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fibers to the hot water is 1:10.
[0190] The final porous fiber has a fineness of 5 dtex, a breaking strength of 5 cN / dtex, and a breaking elongation of 10%; the porous fiber has a porous structure with an average pore size of 150 nm; the specific surface area of the porous fiber is increased by 5 times compared with the blended fiber, and the weight is reduced by 10wt%.
[0191] Comparative Example 3
[0192] A method for preparing a fiber, which differs from Example 5 only in that: in step (2), when preparing the double-end carboxyl polylactic acid oligomer, the amount of waste polylactic acid added is adjusted, and the mass ratio of waste polylactic acid to aliphatic dibasic acid is 75:1, which makes the number average molecular weight of the double-end carboxyl polylactic acid oligomer be 9000 g / mol and the degree of polymerization be 124.
[0193] The breaking strength of the final fiber was 2.3 cN / dtex.
[0194] Compared with Example 5, the breaking strength of the fiber is significantly reduced in Comparative Example 3. This is because the number average molecular weight of the double-end carboxyl polylactic acid oligomer in Comparative Example 3 is too high, which will produce uneven reaction during the repolymerization process, and ultimately cause the molecular weight distribution of the water-soluble polylactic acid to be too wide, resulting in more defects in the internal structure of the fiber, and the arrangement and interaction between the molecular chains become disordered. When the fiber is subjected to external force, the stress cannot be evenly distributed on the molecular chain, and is easily concentrated at the defective site, which makes the fiber more likely to break and reduces the breaking strength.
[0195] Example 6
[0196] A method for preparing a porous fiber, which differs from Example 2 only in that: the intrinsic viscosity of waste polylactic acid is 1.40 dL / g, the aliphatic dibasic acid is adipic acid, the first catalyst is tetrabutyl titanate, and the mass of the first catalyst is 300 ppm of the mass of the waste polylactic acid; when preparing a double-end carboxyl polylactic acid oligomer, the mass ratio of the waste polylactic acid to the aliphatic dibasic acid is 13:1, the reaction temperature is 150°C, and the reaction time is 4h; the number average molecular weight of the obtained double-end carboxyl polylactic acid oligomer is 2000 g / mol, and the nuclear magnetic resonance spectrum is as follows: Figure 1 shown.
[0197] The final porous fiber has a fineness of 4 dtex, a breaking strength of 4 cN / dtex, and an elongation at break of 35%; the porous fiber has a porous structure with an average pore size of 50 nm; the specific surface area of the porous fiber is increased by 12.5 times compared with the blended fiber, and the weight is reduced by 20wt%.
[0198] The above embodiments have been verified that the relative deviation of the number average molecular weight of the double-terminated carboxyl polylactic acid oligomer does not exceed 2%, relative deviation = (|actual value-theoretical value| / theoretical value) × 100%, and the calculation formula of the theoretical value is as follows:
[0199] ;
[0200] In the formula, (Mass of aliphatic dibasic acid), The unit of (mass of waste polylactic acid) is g; (Relative molecular weight of aliphatic dibasic acid), The unit of (theoretical value of number average molecular weight of double-terminated carboxyl polylactic acid oligomer) is g / mol; φ is 17 g / mol.
[0201] Herein, the number average molecular weight is assumed to be an actual value unless the number average molecular weight is explicitly defined as a theoretical value.
Claims
1. A method for preparing a recycled polyester porogen from waste polylactic acid, characterized in that: First, waste polylactic acid and aliphatic dibasic acid are subjected to ester exchange reaction to obtain double-terminal carboxyl polylactic acid oligomers, and then the double-terminal carboxyl polylactic acid oligomers, polyether diols, oligomer diols and inorganic porous materials are mixed and subjected to polycondensation reaction to obtain a recycled polyester porogen containing water-soluble polylactic acid and inorganic porous materials; Aliphatic dibasic acids have 4-20 carbon atoms; The number average molecular weight of the double-terminated carboxyl polylactic acid oligomer is 1000-8000 g / mol; The degree of polymerization of the double-terminated carboxyl polylactic acid oligomer is 12-110; The oligomer diol is obtained by esterification of 5-sodium sulfoisophthalic acid and aliphatic diol; The degree of polymerization of the oligomer diol is 2-5.
2. The method for preparing a recycled polyester porogen from waste polylactic acid according to claim 1, characterized in that: The preparation process of the double-terminal carboxyl polylactic acid oligomer is as follows: waste polylactic acid, aliphatic dibasic acid and a first catalyst are added into a reaction kettle, and the reaction is carried out at 150-220° C. and 0.01-0.3 MPa for 2.5-5 hours to obtain the double-terminal carboxyl polylactic acid oligomer; The mass of the first catalyst is 100-1000ppm of the mass of the waste polylactic acid; the first catalyst is one or more of ethylene glycol titanium, tetrabutyl titanate, ethylene glycol antimony, antimony acetate, antimony oxide, stannous octoate, stannous chloride, zinc acetate and zinc oxide.
3. The method for preparing a recycled polyester porogen from waste polylactic acid according to claim 1, characterized in that: The preparation process of the oligomer diol is as follows: add sodium 5-sulfoisophthalic acid, aliphatic diol and a second catalyst into a reaction kettle, react at 220-240°C and 0.1-0.3MPa until the water output reaches more than 95% of the theoretical water output, thereby obtaining the oligomer diol; The molar ratio of 5-sodium sulfoisophthalic acid to aliphatic diol is 1:1.01-1.1, and the mass of the second catalyst is 0-500ppm of the mass of 5-sodium sulfoisophthalic acid; The reaction was accompanied by stirring at a speed of 100-200 r / min; The aliphatic diol is one or more of ethylene glycol, propylene glycol, butanediol and pentanediol; the second catalyst is one or more of ethylene glycol titanium, tetrabutyl titanate, ethylene glycol antimony, antimony acetate, antimony oxide, stannous octoate, stannous chloride, zinc acetate and zinc oxide.
4. The method for preparing a recycled polyester porogen from waste polylactic acid according to claim 1, characterized in that: The polyether diol is one or more of polyethylene glycol, polypropylene glycol and polytetrahydrofuran, and the number average molecular weight of the polyether diol is 400-4000 g / mol.
5. The method for preparing a recycled polyester porogen from waste polylactic acid according to claim 1, characterized in that: The inorganic porous material is one or more of porous carbon material and porous natural mineral powder, with an average particle size of not less than 0.05 microns and an average pore size of not more than 200 nanometers.
6. The method for preparing a recycled polyester porogen from waste polylactic acid according to claim 1, characterized in that: The total molar weight of the polyether diol and the oligomer diol is 1.0-1.1 times the molar weight of the waste polylactic acid, the molar weight of the oligomer diol is 10-30% of the total molar weight of the polyether diol and the oligomer diol, and the mass of the inorganic porous material is not less than 5% of the mass of the waste polylactic acid.
7. The method for preparing a recycled polyester porogen from waste polylactic acid according to claim 1, characterized in that: The polycondensation reaction includes a pre-polycondensation reaction and a final polycondensation reaction. The pre-polycondensation reaction has a pressure of 0.01-0.1 MPa, a temperature of 170-230°C, and a time of 1-3 h. The final polycondensation reaction has a pressure of 5-300 Pa, a temperature of 180-250°C, and a time of 3-5 h.
8. A regenerated polyester porogen, characterized in that: The method for preparing a recycled polyester porogen from waste polylactic acid as claimed in any one of claims 1 to 7 is adopted; the recycled polyester porogen has a number average molecular weight of 14000-33000 g / mol, a molecular weight distribution index of 1.5-3.0, a melting point of 80-180°C, a crystallization temperature of 25-60°C, and a mass loss rate of 10-75% when immersed in hot water at 50-100°C for 3-30 minutes.
9. The use of a regenerated polyester porogen as claimed in claim 8, characterized in that: After melt-blending and spinning the recycled polyester porogen with fiber-grade polyester to obtain blended fibers, the blended fibers are immersed in hot water at 50-100° C. for 3-30 minutes to obtain porous fibers.
10. The use according to claim 9, characterized in that: The number average molecular weight of the fiber-grade polyester is 15000-40000 g / mol, the mass of the recycled polyester porogen is 2-30% of the total mass of the recycled polyester porogen and the fiber-grade polyester, and the mass ratio of the blended fiber to the hot water is 1:10-50; the fineness of the porous fiber is 1.0-5.0 dtex, the breaking strength is 2.5-5.5 cN / dtex, and the breaking elongation is 10-40%; the porous fiber has a porous structure with an average pore size of 50-300 nm; the specific surface area of the porous fiber is increased by 1.5-12.5 times relative to the blended fiber, and the mass is reduced by 2-30wt%.
Citation Information
Patent Citations
Method for preparing refined level lactide from recovered polylactic acid
CN102746270B
A method for preparing porous structure low melting point composite polyester fiber
CN114775106B
Method for synthesizing lactide by using waste polylactic acid
CN118459435A
Efficient moisture-absorption quick-dry porous polyester fiber, polyester fabric and preparation method of efficient moisture-absorption quick-dry porous polyester fiber
CN118814313A
High-voltage high-crystallization porous stereocomplex polylactic acid material as well as preparation and application of high-voltage high-crystallization porous stereocomplex polylactic acid material
CN117089104A
Cited By
Full-bio-based degradable nylon as well as preparation method and application thereof
CN121181880A